12/15-Lipoxygenase Regulates IL-33-Induced Eosinophilic Airway Inflammation in Mice - Miyata, Jun; Yokokura, Yoshiyuki; Moro, Kazuyo; Arai, Hiroyuki; Fukunaga, Koichi; Arita, Makoto (Frontiers in Immunology, 2021)
Dysregulated fatty acid metabolism is clinically associated with eosinophilic allergic diseases, including severe asthma and chronic rhinosinusitis. This study aimed to demonstrate the role of 12/15-lipoxygenase (12/15-LOX) in interleukin (IL)-33-induced eosinophilic airway inflammation; to this end, 12/15-LOX-deficient mice, which displayed augmented IL-33-induced lung inflammation, characterized by an increased number of infiltrated eosinophils and group 2 innate lymphoid cells (ILC2s) in the airway, were used. Liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based lipidomics revealed that the levels of a series of 12/15-LOX-derived metabolites were significantly decreased, and application of 14(S)-hydroxy docosahexaenoic acid (HDoHE), a major 12/15-LOX-derived product, suppressed IL-33-mediated eosinophilic inflammation in 12/15-LOX-deficient mice. Using bioactive lipid screening, we found that 14(S)-HDoHE and 10(S),17(S)-diHDoHE markedly attenuated ILC2 proliferation and cytokine production in vitro. These findings demonstrate the protective role of endogenous 12/15-LOX-derived lipid mediators in controlling ILC2-mediated eosinophilic airway inflammation and related diseases. Thus, 12/15-LOX-derived lipid mediators may represent a potential therapeutic strategy for ameliorating airway inflammation-associated conditions.